Diabetic Ketoacidosis in A Patient with Type 2 Diabetes On Canagliflozin and Dexamethasone - Lisa D. Alexander, MD; Catherine Yu, MD, FRCPC, MHSc (AACE Clinical Case Reports, 2017)
ABSTRACT: Objective: To describe a case of diabetic ketoacidosis (DKA) associated with sodium-glucose cotransporter-2 inhibitor (SGLT2i) and dexamethasone use in a patient with type 2 diabetes.Methods: We present the case of an 87-year-old male with type 2 diabetes on canagliflozin who underwent resection of a meningioma and received postoperative dexamethasone. Eight days after discharge, he presented to the emergency department with generalized weakness, lethargy, and anorexia.Results: Laboratory investigations revealed hyperglycemia (blood glucose, 39 mmol/L), metabolic acidosis (venous pH, 7.26), an elevated anion gap (22 mmol/L), and positive serum ketones. He was diagnosed with DKA and required admission to the intensive care unit.Conclusion: This is the first report of possible SGLT2i-associated DKA that occurred during co-administration of glucocorticoids. Both SGLT2i and glucocorticoids decrease insulin release and increase glucagon secretion, which may thereby provide an overwhelming ketogenic stimulus. Accordingly, clinicians should exercise caution when co-administering glucocorticoids and SGLT2i until further data are available.Abbreviations: DKA diabetic ketoacidosis; SGLT2i sodium-glucose cotransporter-2 inhibitor